Study on the Prediction of the Height of Two Zones in the Overlying Strata under a Strong Shock. (7th September 2021) - Lai, Xingping; Liu, Bowei; Shan, Pengfei; Cui, Feng; Zhang, Yun; Zhang, Xudong; Bai, Rui; Wu, Xuan
Abstract : A development of overlying strata fractures and an unknown distribution of the two zones, which results from a strong shock tendency roof short-distance coal seam group mining, are the main problems faced by Xiashijie Coal Mine. Consequently, an experiment has been conducted; here are the steps: designing an underlying strata development law and the two-zone distribution physical similarity simulation test under the short-distance coal seam group combined mining, using the BT-AE to comonitor the fracture development law and the distribution characteristics of the caving zone and the water-conducting fractured zone, and combining with 3DEC comparative analysis. The results show that after the coal seam mining is over, the number of overlying fractures increases with depth, controlled by the mining stress field in the direction of 115° west from north to west. The direction of overlying fracture is mainly concentrated in the area of 300° 30°; the overlying fracture angles eventually develop to 81° and 74°, increasing by 15.7% and 8.8%, and the caving ratio and cracking ratio are 4.87 and 17.75. After comparing with the numerical calculation results, the reliability of the two zones obtained by the physical similarity simulation test is verified. The AE analysis results show that the "release-accumulate-release" energy evolution process of overlying rock fracture under mining conditions has a phased relationship with fracture expansion. The energy positioning results are consistent with the distribution of BT observation cracks, and the large energy events are mostly concentrated in the collapse zone, indicating that AE has the practicality of disaster warning. The results of this study provide scientific guidance for water-preserving mining under the combined mining of coal seams with a strong impact tendency roof in Xiashijie Coal Mine.